Comparison between Intravitreal Bevacizumab and Triamcinolone Acetonide in Management of Diabetic Macular Edema - Simon A Siregar; Elvioza Elvioza; Andi A Victor; Ari Djatikusumo; Gitalisa A Andayani; Anggun R Yudantha (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2016)
Background: To critically evaluate the efficacy and safety profile of intravitreal bevacizumab (IVB)compared to intravitreal triamcinolone acetonide (IVTA) in patients with diabetic macular edema(DME).Methods: We searched publication related to diabetic macular edema managed by bevacizumab andtriamcinolone acteonide through systematic search of database in a period of January 2002 untilOctober 2013. Information needed from all articles were extracted into a data extraction sheet. Wereviewed the efficacy of both treatment in decreasing central macular thickness (CMT), improvementof visual acuity and the adverse effects following the injection.Results: Twelve articles were included after fulfilling inclusion and exclusion cirteria. Our analysisshowed single IVTA injection were more effective in decreasing CMT and improving visual acuity at1 week to 3 months. There were no significant improvement of CMT in multiple injection of IVTAcompared to multiple injection of IVB.Conclusion: A single intravitreal injection of IVTA appears to offer certain short-term advantagesover IVB for the management of patients with diabetic macular edema, particularly with regard toCMT.Â Keywords: intravitreal, triamcinolone acetonide, bevacizumab, diabetic macular edema